Civil Law, Conflict of Laws, and Extraterritoriality in the European Supply Chain Due Diligence Law - Koos, Stefan (Hasanuddin Law Review, 2024)
This paper gives an overview of the new European Union’s Corporate Sustainability Due Diligence Directive (CSDDD), its relation to the German Supply Chain Due Diligence Act (LkSG) from 2021, and the systematic background of both acts. The article contradicts criticism of the extraterritorial effects of the acts, underlining a legislative purpose as part of the national business law regarding fair competition and consumer protection besides the purpose of improving life conditions. The acts are part of an international socially responsible business law. The CSDDD is introducing a new specific civil liability provision. It also brings significant advancements in conflict-of-law principles by introducing mandatory liability norms that apply regardless of jurisdiction. Implementing due diligence obligations in complex international supply chains poses challenges for companies, requiring robust risk management systems and ongoing adjustments. This strict regulation must be balanced with the practical feasibility of Corporate Social Responsibility duties, and a reasonable allocation of responsibilities must take place without risking that the effect of the legislation will stay behind formalistic compliance requirements. The concept of organizational responsibility plays a core role in this balancing process.